Ausência congénita de estribo e janela oval com nervo facial mal posicionado e tuba auditiva anómala. - Álvarez-Buylla Blanco, Mercedes; Álvarez-Buylla Camino, Miguel (Revista Portuguesa de Otorrinolaringologia-Cirurgia de Cabeça e Pescoço, 2019)
Introduction: Since in 1995 the first case of absence of stapes was described, several cases were reported. However, its etiology remains unknown. Some authors suggest a genetic cause, without excluding the possibility of embryopathy due to infections or chemical agents. The existence of an associated palatal cleft, in this case, reinforces the hypothesis of a multifactorial origin. Objective: Describe a rare condition in order to know how to suspect it. This condition is frequently associated with facial nerve malposition, that difficult the surgery and so, the most frequent treatment is providing hearing aids or a bone anchored hearing aid. Case report: We present a case of a 10 years old girl who complains of left hearing loss since childhood, accompanied by tinnitus and frequent left ear otorrhea episodes. We studied symptoms, complementary exams, treatment and course. Discussion and conclusions: A middle ear malformation should be suspected with the presence of a history of conductive hearing loss since birth or more frequently between the 7 and 12years old, fixed-type, which often affects conversational or low frequencies, which are more intense than other acquired hearing loss, with no history of ear infections or without improvement despite different kinds of treatments, and with a family history of hearing loss. Conclusion: Congenital absence of stapes and oval window associated with anomalous course of the facial nerve is a rare entity. It presents as a conductive hearing loss non-progressive with 60 dB tone air threshold, often presented during childhood. Diagnosis is based on clinical suspicion by a correct medical history and audiological examination, confirmed by Computed Tomography (CT) scan. The anomalous course of the facial nerve supports the diagnosis and guides treatment. Initial treatment with hearing aids provides good hearing gain with adequate adaptation.